Analisis Penyebab Penyebaran Eceng Gondok (Eichornia crassipes) di Daerah Pesisir Pantai, Desa Tempel, Demak, Jawa Tengah beserta Alternatif Solusinya - Cahyo Wulandari; Shelly Septia Ilhamy; Muhammad Afif Syaifurrahman; Ghina Zain Sukmaningrum; Muhammad Nurhafiz Sidiq; Muhammad Mukhlas Cahyadi (Direktorat Pengabdian kepada Masyarakat, 2023)
Tempel Village, located in Demak Regency, Central Java, is an example of a village whose waters experience eutrophication or the enrichment of water bodies from minerals and nutrients, which is characterized by the uncontrolled growth of water hyacinth weeds. This is due to the delivery from the river flow in the area above which is added with excess nutrients from the rice fields. One way to deal with eutrophication is by reducing the use of inorganic fertilizers or replacing them with organic fertilizers. The implementation of this community education program aims to increase public awareness of the existence of water hyacinth weeds which have a negative impact on the ecosystem and their solutions. The method of implementing activities includes field observations followed by outreach and training with related parties. The outreach was carried out to provide information about the causes of water hyacinth due to eutrophication related to agricultural problems. Activities continued with the Clean River program to reduce water hyacinth biomass. The training includes making compost and liquid organic fertilizer as well as biobriquettes from water hyacinth. The results of the final discussion regarding inviting program work showed that public understanding of the water hyacinth problem had increased from the results of the initial discussion before this series of outreach activities was held. It is hoped that this community outreach program can increase the knowledge of the people of Tempel Village in understanding the negative impacts of water hyacinth as a weed and how to handle it to balance the ecosystem and prevent flood disasters.